Предмет: Алгебра,
автор: wetaliisydorenko05
Решить уравнение
lg(2x-3)=>lg((x^2)+4x)
Приложения:
Ответы
Автор ответа:
1
lg(2x - 3) = lg(x^2 - 4x + 2)
ОДЗ 2х - 3 > 0, x^2 - 4x + 3 > 0
x^2 - 4x + 2 = 2x - 3
x^2 - 6x + 5 = 0
По теореме Виета
х₁ = 1 не удовлетворяет, т. к. 2*1 - 3 = -1 < 0
х₂ = 5 удовлетворяет, т. к. 2*5 - 3 >0 и 5^2 - 4*5 + 2 > 0
Ответ 5
wetaliisydorenko05:
Это другое задание, не подходит
Похожие вопросы
Предмет: Алгебра,
автор: ogfyyuuu
Предмет: Окружающий мир,
автор: kmelnik257
Предмет: Математика,
автор: elizavetanuzhnaya230
Предмет: Русский язык,
автор: bombat27
Предмет: История,
автор: pavlovamilana099